PROFILE OF STYLE AND QUALITY OF LIFE OF PROFESSIONALS OF A GYM CENTER AT BARRA DA TIJUCA (Fiep Bulletin - online, 2012)
The Physical Education professional can be considered the most representative active in education for a healthier lifestyle, the practice of prescribing appropriate exercise and basing on the example and authenticity. The present study of interest to evaluate and correlate the style and quality of life for Physical Education professionals working in a large gym in the neighborhood of Barra da Tijuca in different areas. The type of research used was descriptive and correlational. To this end, 51 professionals (74.5% men and 25.5% women) with mean age of 30.88 ± 6.46 years and average time to graduate from 5.80 ± 6.42 years were evaluated through the questionnaires already validated Lifestyle Nahas and WHOQOL-bref. For the Lifestyle Nahas, professionals surveyed had a very positive opinion in the fields Nutrition, Physical Activity, Preventive Behavior, Relationships and Stress Control. Only behaviors assessed in the third issue of the domains Physical Activity and Stress Control danger to the health and affect their quality of life. For the WHOQOL-bref, the means obtained in the physical, psychological and social relations have been characterized as a success; already in the environment domain, the mean measurement uncertainty was considered. This may be a reason for self-evaluation of individuals with regard to quality of life was lower than that of their own health. It can be considered a despautério the fact that they have been evaluated for professionals of the issues in the field of physical activity Lifestyle Nahas a score that characterizes health risk and affects the quality of life, since the physical domain of WHOQOL -bref had an average that can be characterized as successful. Further studies are needed to better understand the reality of this group and propose interventions to improve it.
Keywords: Quality of life; Lifestyle; Professional Physical Education